1954
DOI: 10.1002/aja.1000950207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of locally applied vitamin a and estrogen on the rat vagina

Abstract: The rodent vaginal epithelium is of special interest as a target organ for studying the interaction of endocrine and dietary factors. One of the earliest and most reliable manifestations of a deficiency of vitamin A is the continued cornification of the vaginal epithelium in the rat. Similarly, the rodent vaginal epithelium undergoes marked keratinization and stratification under the influence of estrogenic stimulation.Little is known regarding the basic factors underlying normal and abnormal vaginal cornifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1955
1955
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The findings that vitamin A removes the keratin from oestrogen-stimulated vaginal epithelium in the rat [Kalm and Berne, 1950;Kahn, 1954] were duplicated in this study in the mouse. The vitamin does not inhibit the hyperplasia induced by oestrogen [Martin and Claringbold,I960].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The findings that vitamin A removes the keratin from oestrogen-stimulated vaginal epithelium in the rat [Kalm and Berne, 1950;Kahn, 1954] were duplicated in this study in the mouse. The vitamin does not inhibit the hyperplasia induced by oestrogen [Martin and Claringbold,I960].…”
Section: Discussionmentioning
confidence: 62%
“…Kahn and Bern [1950] have shown that intravaginal injections of crystalline vitamin A alcohol, in an oil vehi cle, inhibit keratinization that is induced by oestrogen stimulation in the vaginal epithelium of spayed rats. The epithelium is equivalent in thickness to that produced by oestrogen stimulation alone, but keratinization is absent [Kahn, 1954]. Neither vitamin A and oil, nor the oil vehicle alone, produces a significant increase in epithe lial thickness or keratinization.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…If this were the case, one would predict a more rapid onset of the persistent oestrous-like symptoms than seen in our experiments ; 2 months of treatment (Table 1) should have been sufficient. Vitamin A deficiency has been shown to produce a keratinized vaginal mucosa (Evans & Bishop, 1922) and local application of vitamin A to the vagina opposes the keratinizing effects of large doses of oestro¬ gen; glycoprotein synthesis is favoured and the epithelium becomes mucified (Kahn & Bern, 1950;Kahn, 1954). The early vaginal opening in the rats treated with 5000 i.u.…”
Section: Discussionmentioning
confidence: 99%
“…On vaginal epithelium of the adult rat, vitamin A, either topically applied (Kahn, 1954) or orally administered (Hohlweg, 1951), appears to exert an effect antagonistic to that of oestrogen. A similar effect has been noted on mouse vaginal epithelium in vitro (Lasnitzki, 1961).…”
mentioning
confidence: 99%